Pepsin extracted from the proventriculi of geese raised under different fattening techniques and its effect on microbiological quality and cheese production - Beyazgül, Pelin; Tonbak, Fadime; Özmen, Görkem Kirmizikaya; Baykalir, Yasin; Şimşek, Ülkü Gülcihan; Arslan, Ali; Yilmaz, Ökkeş (Federal University of Lavras, 2026)
Goose pepsin is critically important in cheese coagulation, both in terms of variety and economics. This study was conducted to investigate the potential use of the pepsin enzyme obtained from the proventriculi of geese reared under intensive and extensive fattening systems as a milk coagulant, and to evaluate its effect on the quality of white brined cheese. A total of 10 groups of cheeses (2 feeding systems × 5 levels of enzyme concentration) were produced using pepsin derived from intensively and extensively reared geese, together with chymosin (calf rennet) in the following ratios: 100% chymosin, 50% chymosin+50% pepsin, 75% chymosin+25% pepsin, 25% chymosin+75% pepsin, and 100% goose pepsin. Samples were stored at 4±1°C and chemically and microbiologically analyzed on days 0, 7, 15, 30, 45, 60, 90, and 120 of storage. During storage, a significant decrease was observed in other bacterial counts, while an increase was noted in the counts of psychrotrophic, lipolytic, and proteolytic microorganisms (P<0.05). No E. coli growth was detected (<1.0 log CFU/g). Differences in microbiological counts between enzyme groups and storage days were statistically significant (P<0.05). Notably, the groups containing 100% goose pepsin exhibited superior microbiological quality parameters (P<0.05). In terms of chemical parameters, apparent pH decreased during storage, while percentage of lactic acid (% l.a.) and salt content increased (P<0.05). However, no significant differences in apparent pH, acidity, or salt were observed among the experimental groups, regardless of feeding system or enzyme combination (P<0.05). © 2026, Federal University of Lavras. All rights reserved.
Pepsina extraída de proventrículos de gansos manejados sob diferentes técnicas de engorda e seu efeito na qualidade microbiológica e fabricação de queijos
Keywords: Intensive-extensive handling; quality parameters; white brined cheese